Nilai-nilai Multikulturalisme Tradisi Kupatan di Desa Plosoarang Kecamatan Sanankulon Kabupaten Blitar - Fadli, Rizky Very (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2022)
Abstract: Indonesia is a nation that has various ethnic groups, languages, customs and religions. One form of custom or tradition that is still carried out today is the kupatan tradition. The kupatan tradition is practiced by the Javanese people of Plosoarang Village, Sanankulon District, Blitar Regency which is held in the month of Shawwal to express gratitude to God for the blessings given. The implementation of the kupatan tradition contains exemplary values ​​such as the value of multiculturalism. This is what fosters a sense of security, peace, tolerance, mutual cooperation between residents. The writing of this article uses qualitative research with the literature study method in examining the existing problems. In writing this article, it is hoped that the Kupatan tradition which is an ancestral heritage can be preserved because it has multiculturalism values ​​that can be imitated in social life. Keywords: Multiculturalism, Tradition, Kupatan.